The Effect of Hedonic Shopping Motivation and Shopping Lifestyle on User Impulse Buying Shopee E-Commerce (Study on Majalengka University Students) - Widia Yunengsih; Pipih Sopiyan; Rina Masruroh (Finance and Business Management Journal, 2023)
The progress of e-commerce is growing rapidly. One of the e-commerce that is often used by students at Majalengka University is the e-commerce Shopee. The high use of e-commerce Shopee among students results in impulse buying. This study aims to determine the effect of Hedonic Shopping Motivation and Shopping Lifestyle partially on the Impulse Buying of e-commerce Shopee users at Majalengka University students. This study uses a quantitative method with the type of survey research using a descriptive analysis approach and verification analysis. The population in this study were Shopee e-commerce users at Majalengka University students, with a sample of 100 respondents. The sampling technique used is incidental sampling. This study uses a Likert scale. Data analysis using classical assumption test, multiple linear regression analysis, coefficient of determination, model feasibility test, and hypothesis testing using the partial test. The results of the research that have been carried out show that Hedonic Shopping Motivation is in the high category, Shopping Lifestyle is in the high category and Impulse Buying is in the medium category. Hedonic Shopping Motivation and Shopping Lifestyle have a positive and significant effect partially on the Impulse Buying of Shopee e-commerce users.